Obesity paradox and aging: Visceral Adiposity Index and all-cause mortality in older individuals: A prospective cohort study - Wang, Lei; Yi, Zhong (Frontiers in Endocrinology, 2022)
Background According to several research findings, the link of body mass index (BMI) with mortality for older adults differs from that for younger adults. In older adults, a low BMI is linked to a higher chance of mortality. However, the link of visceral adiposity index (VAI) with all-cause mortality among the elderly is still unknown. Methods The present prospective cohort study included 2-year data from 1999 to 2014 provided by the National Health and Nutrition Examination Survey (NHANES) in the United States. NHANES participants at or above the age of 65 were included. From the start of the survey to the end of December 2015, mortality-related follow-up statistics are available. Univariate- and multivariate-adjusted Cox proportional hazard models were estimated for VAI, and the results were presented as regression coefficients and 95% confidence intervals (CI). Results The 82,091 NHANES participants represented 442.2 million non-institutionalized residents of the United States. A total of 11,173 older individuals (representing 23.3 million; aged 73.4 ± 5.8 years; 56.3% women, 82.7% non-Hispanic Whites, 6.8% non-Hispanic Blacks, and 3.3% Mexican Americans) were included in the study. During the 80-month follow-up period, 4466 fatalities were reported, including 825 deaths from cancer, 867 from heart disease, and 211 from cerebrovascular disease. The restricted cubic spline model demonstrated a robust J-shaped link between VAI and all-cause mortality, revealing a significant decrease in risk within the lower range of VAI, which attained the lowest risk close to 1.7. With VAI greater than 1.7, the risk of mortality increased with the increase of VAI (P for non-linearity = 0.025). In the multivariate-adjusted model, the risk of all-cause mortality was 0.73 (0.56-0.97) and 1.05 (1.01-1.09) in participants with VAI less than 1.7 and VAI greater than or equal to 1.7, respectively. Conclusion This investigation is a population-based cohort study with high sample sizes and a long-term general-population follow-up that showed a J-shaped link between VAI levels and all-cause mortality. Understanding the independent roles of VAI in the relationship between BMI and mortality is crucial to understanding the obesity paradox phenomenon.